Social inequality forms, causes, and consequences - Fitz Gibbon, Heather M.; Hurst, Charles E.; Nurse, Anne 1968- (Routledge Books, 2023)
The eleventh edition of Social Inequality: Forms, Causes, and Consequences is an introduction to the study of social inequality. Fully updated statistics and examples convey the pervasiveness and extent of social inequality in the United States. The authors use an intersectional perspective to show how inequality occurs, how it affects all of us, and what is being done about it. With more resources and supplementary examples, exercises, and applications embedded throughout to aid students' learning and visualization of important concepts, the book provides a rich theoretical treatment to address the current state of inequality. In line with current affairs, the authors have expanded the content to include: An intersectional approach throughout the chapters; A stronger emphasis on the connections between poverty, wealth, and income inequality; New case studies on the opioid epidemic, COVID-19, the lead poisoning crisis, and climate change; A new focus on the rise of right-wing movements. Social Inequality is an invaluable introduction to the study of social inequality from a sociological perspective for undergraduate students and the general public"--